Deciphering recovery paradigms: Foam rolling's impact on DOMS and lactate dynamics in elite volleyball athletes - Xin Zhang; Xin Li; Zhizheng Wu; Xuan Li; Guangyi Zhang; Xin Zhang (Heliyon, 2024)
This study examines the effects of Self-Myofascial Release (SMR) techniques on post-exercise recovery in elite volleyball athletes. Through a controlled investigation involving eighteen Chinese Men's National Volleyball Team athletes, the research assessed the impact of foam rolling (FR) versus passive recovery (PAS) on blood lactate clearance and Delayed Onset Muscle Soreness (DOMS), as measured by Visual Analogue Scale (VAS) scores. Findings indicated that FR significantly reduces VAS scores and facilitates lactate clearance when compared to PAS, suggesting foam rolling may enhance post-exercise recovery. While confirming foam rolling's benefits, this research calls for further exploration into recovery mechanisms, emphasizing a cautious interpretation of foam rolling as part of a comprehensive recovery strategy.